A Case report of a kid with Fibrodysplasia ossificans progressiva (FOP) and literature review for management of FOP (Journal of Pakistan Orthopaedic Association, 2023)
Fibrodysplasia ossificans progressiva is a connective tissue disorder in which connective tissues (ligaments, tendons) are gradually ossified and replaced by bone, there is extra skeletal bone formation. Any trauma can aggravate ossification in soft tissue. This condition usually is noticed at childhood. There is restriction of movements in major joints.We report a case of 2 years old boy with fibrodysplasia ossificans progressiva, who was brought by his parents to our OPD with history of swelling on back, scapular region and forehead for last 4 months. Parents also reported limitations of movements in spine and bilateral shoulders. Radiographs shows heterotrophic ossification in paraspinal muscles of dorsolumbar spine, and latissimus dorsi and trapezius muscle. Clinical and radiological evidence was of Fibrodysplasia ossificans progressiva. Treatment strategy is mainly based on prevention of trauma or injury, educating parents about the disease and medical management for acute painful episodes.